The first finding of parasitic mite, Parasteatonyssus nyctinomi (Mesostigmata: Gamasina: Macronyssidae), in Namibia - Orlova, Maria V. (J S Afr Vet Assoc, 2020)
Sixty-four individuals of a macronyssid mite, Parasteatonyssus nyctinomi (Zumpt, Patterson 1951), were identified from Egyptian free-tailed bats Tadarida aegyptiaca (É. Geoffroy 1818) (Chiroptera: Molossidae) captured in the Kunene region of Namibia (southern Africa). This is the first report on P. nyctinomi in the country.